LITERATURE REVIEW FAKTOR-FAKTOR YANG BERKETERKAITAN DENGAN KEJADIAN SCABIES PADA ANAK - PUTRI SEPTIANI; Miftah Apriani; Dewi Ciselia (Jurnal Kesehatan Abdurrahman, 2026)
Scabies is a skin disease commonly found in tropical and subtropical climates and is contagious. Another word commonly used by Indonesians to describe scabies is "kudis," while in Javanese it is called "gudig," while in Sundanese it is called "budug." According to Kusuma (2021), this disease, caused by the parasite Sarcoptes scabiei variant hominis (a type of mite), is also commonly known as body lice, budukan, or gatas agogo. Symptoms of scabies are typically characterized by intense itching, a rash similar to acne, and scales or blisters on the skin. Generally, scabies can be transmitted through direct physical contact or the use of shared objects such as toiletries. A common complication of scabies is a secondary infection caused by bacteria entering through scratches. Excessive itching causes a person to scratch, creating wounds, which can become entry points for infection-causing bacteria.